Bruce Almighty [videorecording (DVD)] - Shadyac, Tom; Carrey, Jim, 1962-; Freeman, Morgan; Aniston, Jennifer; Hall, Philip Baker, 1931- (Universal, 2003)
Bruce Nolan is a discontented TV reporter who believes the entire universe is stacked against him. After a bad day, Bruce flies into a rage and blames God for making his life so miserable. God responds by endowing Bruce with all of His divine powers and challenges him to take on "The Big Job" to see if he can do it any better.